CITRA PEREMPUAN DALAM KUMPULAN CERPEN PEREMPUAN YANG MEMESAN TAKDIR KARYA W. SANAVERO - Mery Suryanti; Ahmad Rabi'ul Muzammil; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The purpose of this study is to describe the image of women in the collection of short stories Women Who Order Takdir by W. Sanavero. This research was conducted qualitatively using content analysis and descriptive methods. The data source of this research is a collection of short stories Women Who Order Takdir by W. Sanavero with data in the form of quotes, phrases, and sentences that lead to the object of analysis. The results of this study indicate that the data collected is based on aspects of the image of women in W. Sanavero's 16 short stories Women Who Order Takdir, namely the physical image of women, the psychological image of women, and the social image of women (images of women in the family and society).In the physical image of women, an image is obtained with the criteria of having facial features, body condition, and household activities. The psychological image of women is obtained with the criteria of having a responsible nature, daring to make decisions, being able to distinguish what is important and what is not important, realistic, has a good nature, and is not easy to judge. The image of women in the family is obtained with the criteria of women as children, women as wives, and women as mothers. The image of women in society is obtained with the criteria of women who have interpersonal relationships and personal relationships with the community.